A COMPARATIVE STUDY ON INDONESIA MINIMARKET PRIVATE LABEL BRANDS - Cahyani Pratisti (Universitas Pakuan, 2023)
ABSTRACTThis study aims to identify differences in consumer perceptions regarding product quality, price perceptions, and perceived value of Indomaret and Alfamart private label products. The population is consumers of private-label products belonging to Alfamart and Indomaret in Indonesia. There are 200 consumers as a sample of this study that took by nonprobability sampling with purposive sampling methods. The study analysis method uses variant Levene's similarity test. The study results show that there are differences regarding the perceived quality, perceived price, and perceived value of Indomaret and Alfamart private-label products. Consumers prioritize quality over price so it becomes an opportunity for private label products to always provide better quality products than before.ABSTRAKPenelitian bertujuan untuk mengidentifikasi perbedaan persepsi konsumen mengenai kualitas produk, persepsi harga, dan persepsi nilai produk private label merek Indomaret dan Alfamart. Populasi dalam penelitian ini adalah konsumen produk private label milik Alfamart dan Indomaret di Indonesia. Sebanyak 200 orang konsumen diambil secara nonprobalility sampling dengan purposive sampling methods. Analisis data menggunakan metode analisis Variant Levene's. Hasil penelitian menunjukkan bahwa terdapat perbedaan mengenai persepsi kualitas, persepsi harga dan persepsi nilai. Konsumen lebih mementingkan kualitas dibanding dengan harga sehingga menjadi peluang bagi produk private label untuk menyediakan produk yang semakin berkualitas.